Diversité Inter Décennale De La Végétation De La Vallée De Goulbi N’Kaba - Souley, Mahaman Hamissou Illo; Saley, Karim; Chaibou, Issa; Moussa, Boubacar M.; Mahamane, Ali; Saadou, Mahamane (European Scientific Journal, ESJ, 2018)
The present study is conducted in the Sylvo-Pastoral Zone (ZSP) of the Goulbi N’Kaba Valley and the agricultural zone (fields on adjacent terraces), in the southern center of Niger. The objective of the study is to evaluate the inter-decennial plant biodiversity (2004-2014). Thus, the phytosociological surveys (Daget and Poissonet, 1971) were carried out in plots of 2500 m², along the 6.5 km transects following stratified sampling. An ascending hierarchical classification, followed by an ordination by Nonmetric Multi-dimensional Scaling (NMS) allowed to identify the plant groups. The diversity of each group was evaluated. The results show that the families of Poaceae and Fabaceae are the most abundant in 2004 (15.58% and 11.69%) and in 2014 (18.75% and 7.29%). However, compared to the genera, Indigofera (10.53%), Cassia (6.58%), Acacia (5.26%), Aristida (5.26%) are the most abundant in 2004, while Aristida (4 , 17%), Cassia (4.17%), Spermacoce (3.13%), in 2014. Three groups (mixed, fields, ZSP) have been identified. The 2004 and 2014 index, of Margalef (18,38 and 11,28), Menhinick (2,55 and 1,52), Shannon-Weaver (4,77 and 4,14), the fairness of Pielou (0, 66 and 0.63), the Simpson index (0.89 and 0.91) and Hill (0.95 and 0.93) are high in all the groups, mixed, fields and ZSP (respectively for G1, G2 and G3). But the beta diversity (Whittaker (24), Jaccard (0.52), Sorensen (0.69) index) for each of these groupings remains low. There was no significant change in inter-decennial diversity at the Guidan Tawayé and Korin Habdjia sites from 2004 to 2014.